PELATIHAN DENGAN STRATEGI SWOT PADA UKM DI KOTA TANGERANG - Nawawi, M.Tony; Darryl (Jurnal Serina Abdimas, 2024)
Everyone who opens a business, whether in the form of products or services, should expect to make a profit. Therefore, he must try to maintain the continuity of his business. One way to maintain your business is to use a business strategy, namely a SWOT analysis strategy. With this SWOT analysis, he can find out the strengths, weaknesses, opportunities and threats that will be faced in the future. This PKM activity aims to help Home Businesses (UKM) explain the importance of SWOT analysis strategies in running their business. This PKM partner is a home-based business engaged in the culinary business, where this business activity has been carried out since 1996 with limited capital and is carried out by using a cart going from complex to complex. Over time, now the partner's business has a permanent location at home, although it is not yet optimal. In implementing partner businesses, of course they face many obstacles, for example business capital problems, marketing strategy problems, and a lack of knowledge about business. For this reason, this PKM activity is carried out with the aim of helping partners increase their knowledge in terms of introducing business strategies with SWOT analysis, so that they know their Strengths, Weaknesses, Opportunities and Threats optimally. The method offered in this activity is offline training/socialization. The material that will be presented includes: a brief explanation of the SWOT business strategy, the importance of SWOT, SWOT elements, and SWOT strategy assessment criteria and others. With this socialization, it is hoped that partners can overcome their problems, and partners can understand the need to carry out a SWOT analysis strategy in running their business.